Crustal deformation in the Rio de la Plata estuarine (South Atlantic passive margin) and the associated seismicity as a consequence of an isostatic readjustment - Godoy, Laura Beatriz (2020)
The Río de la Plata estuarine has been the epicenter of the 30 November 2018 intra-crustal earthquake with a magnitude and focal depth of 3.7 and 19 km (±6 km), respectively, which alerted the Buenos Aires city population. This area has also been the locus of a series of earthquakes with magnitudes ranging from 3.7 to 5, and particularly the 1888 earthquake, probably with an epicenter near the axis of the estuarine. These earthquakes occur in the Salado basin area, an aulacogen basin associated with the early stages of the South Atlantic spreading in late Early Cretaceous times, that subsided all through the Cenozoic. Previous gravimetric analyses revealed that this basin is characterized by an important crustal attenuation zone. From a new gravimetric analysis, using satellite gravity data, we find isostatic anomalies associated with this section of the Atlantic passive margin. Therefore, we propose that the origin of these earthquakes is the isostatic readjustment of this aulacogen type basin, a process that could have reactivated shallow crustal structures. From a preliminary evaluation, we estimate that the Salado basin would subsidize other ~2 km to compensate for the measured thick anti-root, constituting a crucial seismogenic source that should be considered due to the demographical and economic importance of the region.